The global transcriptional regulator MgaSpn affects the virulence of Streptococcus pneumoniae by regulating PcpA - Shuhui Wang; Tianyi Xu; Ye Tao; Li Lei; Xuemei Zhang; Yibing Yin; Yuqiang Zheng (BMC Microbiology)
Abstract The global transcriptional regulator MgaSpn is a significant virulence factor of Streptococcus pneumoniae. In our previous study, we found that MgaSpn is a regulator of bacterial virulence by modulating the levels of phosphorylcholine (ChoP) and capsular polysaccharides (CPS) on the surface of S. pneumoniae. Here, we report for the first time that pcpA expression was significantly increased in mgaSpn deletion strains and significantly decreased when mgaSpn was overexpressed. Electrophoretic mobility-shift and DNase I footprinting assays confirmed that MgaSpn interacts with the pcpA promoter (P pcpA ) at two specific binding sites. Virulence experiments demonstrated that the interaction between MgaSpn and PcpA is necessary for pneumococcal colonization and invasive infection. Western blot analysis indicated that iron concentration can influences the regulation of PcpA expression via MgaSpn. In summary, these results revealed that MgaSpn regulates PcpA and plays a significant role in pneumococcal pathogenesis.